The Influence of Musyarakah and Mudharabah Financing of Profitability at BCA Syariah - Suhara, Edi (Indonesian Scientific Publication, 2024)
This study aims to determine the effect of musharakah financing and mudharabah financing on the profitability of Bank BCA Syariah for the 2018-2022 period, both simultaneously and partially. Data analysis techniques in this study use quantitative methods and secondary data. The population in this study is all financial statements of Bank BCA Syariah since its establishment until now. The sample used is the quarterly report of Bank BCA Syariah for the 2018-2022 period. The data analysis used is multiple linear regression analysis, classical assumption test, and hypothesis test. The results showed that: (1) simultaneously musharakah financing and mudharabah financing have a positive and significant effect on profitability. The results of the F test show Fcalculate > Ftable (6.613 > 3.59) with sig (0.010 < 0.05) (2) Musharakah financing has a positive and significant effect on profitability. The results of the T test showed Tcalculate > Ttable (3.22 > 1.749) with sig (0.005 < 0.05) and the results of multiple linear regression showed 0.026. (3) Mudharabah financing has a negative and insignificant effect on profitability. the results of the T test showed Tcalculate > Ttable (-1.539 < 1.749) with sig (0.142 > 0.05) and multiple linear regression results showed -0.098